Optimasi Kualitas Tenaga Listrik Di Area Banyuwangi Menggunakan Radio Gateway Over Internet Protocol - Machrus Ali; Dwi Ajiatmo; Muhlasin (Universitas Darul Ulum, 2020)
One of the communication problems at PLN is communication in areas that are not covered by radio frequencies. With the limitation related to radio frequency because the blankspot can have an impact on the speed of service, both in terms of recovering when disturbances occur, communication for coordination between officers, and maintenance work. Meanwhile, efforts to expand radio frequency coverage areas by building tower repeater links and BTS tower rentals require relatively large costs. Information technology that is developing now makes it easy for everyone to communicate through various media, one of which is an internet connection. Widespread development of infrastructure owned by telecommunications providers, the wider availability of internet connections in the blank spot area. To overcome the blank spot areas that have an impact on SAIDI and SAIFI, Radio Gateway Over Internet Protocol is used in the working area of ​​PT. PLN (Persero) Banyuwangi area that connects communication radios with mobile phones through the internet network. From the calculation using the average formula in the Microsoft Excel program the average value of SAIDI is better than before. Meanwhile, the average SAIFI score afterwards is also better than before. By using the T-Test test analysis it is known that the calculated t value is better, and for SAIFI it is known that the calculated SAIDI data is also better.